2008
DOI: 10.1126/science.1159505
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the MicroRNA Pathway by Bacterial Effector Proteins

Abstract: Plants and animals sense pathogen-associated molecular patterns (PAMPs) and in turn differentially regulate a subset of microRNAs (miRNAs). However, the extent to which the miRNA pathway contributes to innate immunity remains unknown. Here, we show that miRNA-deficient mutants of Arabidopsis partly restore growth of a type-three secretion-defective mutant of Pseudomonas syringae. These mutants also sustained growth of non-pathogenic Pseudomonas fluorescens and Escherichia coli strains, implicating miRNAs as ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
289
0
23

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(322 citation statements)
references
References 29 publications
10
289
0
23
Order By: Relevance
“…SRO5 along with PYRROLINE-5-CARBOXYLATE DEHYDROGENASE (an overlapping gene in the antisense orientation) generate 24-and 21-nucleotide siRNAs, which together are components of a regulatory loop controlling reactive oxygen species production and stress response (Borsani et al, 2005). Similar suppression of the host miRNA machinery by bacterially derived effector proteins has recently been demonstrated in Arabidopsis (Navarro et al, 2008).…”
Section: Regulation Via Other Tfs and Proteinsmentioning
confidence: 95%
“…SRO5 along with PYRROLINE-5-CARBOXYLATE DEHYDROGENASE (an overlapping gene in the antisense orientation) generate 24-and 21-nucleotide siRNAs, which together are components of a regulatory loop controlling reactive oxygen species production and stress response (Borsani et al, 2005). Similar suppression of the host miRNA machinery by bacterially derived effector proteins has recently been demonstrated in Arabidopsis (Navarro et al, 2008).…”
Section: Regulation Via Other Tfs and Proteinsmentioning
confidence: 95%
“…This process would facilitate the continuing amplification and diversification of R genes. Both bacteria and viruses have evolved effectors that can suppress miRNA and siRNA pathways (32,33). In addition to contributing to pathogen spread, the temporal shutdown of miRNA and siRNA function by pathogen effectors might also enhance Rgene function by blocking the formation or activity of the R-gene targeting miRNAs and, thus, provide some balance to resistance and susceptibility during host-microbe interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of how effectors modulate plant immunity is largely unclear, especially in RNA interference (RNAi)-involved pathways which usually play pivotal roles in both plant immunity as well as pathogen infection (Bozkurt et al 2012; Qiao et al 2013). Previous study identified Pseudomonas syringae effectors that suppress transcriptional activation of PAMP-responsive micro RNAs (miRNAs) or miRNA biogenesis, stability or activity, and Arabidopsis miRNA-deficient mutants partly restored growth of P. syringae secretion-defectivemutant (Navarro et al 2008). Hundreds of predicted effector genes from oomycete genomes reflect more complex defence–counterdefence crosstalk than that in plant–bacteria interactions (Thines and Kamoun 2010; Qiao et al 2013).…”
Section: Introductionmentioning
confidence: 99%